Análise da recuperação de açúcares redutores totais na etapa de filtração de uma usina sucroalcooleira - Rodrigues, Gustavo Arnaldo (Universidade Federal de São Carlos, 2022)
Brazil is the largest sugarcane producer of the world, with more than 654 millions tons harvested in the year of 2021. In the same year, were produced 35 millions tons of sugar and 26,8 billions liters of ethanol. Due to the production size, losses in process results in big financial damage. Among the process macro steps are the juice treatment, that seeks to eliminate insoluble solids and contribute with the product’s final quality. The filtration is the last part of the treatment, which the mud that came from the clarifier is filtered aiming to recover total reducing sugars (TRS). An adequate control and sizing are necessary to minimize the effects of losses in filtered mud. Thus, this work’s goal was to evaluate the recuperation of TRS from different scenarios in the unit, which has four rotary vacuum filters and one vacuum belt filter. In the scenarios, the occupancy of the filters was varied and, posteriorly, the amount of TRS, the filter loss and the financial recovery were calculated. Comparing with the most efficient scenario, where both filters was under full capacity, the scenario in which the rotary filters where 25,06% above capacity, presented mud filter loss of 0,137% resulting in a financial loss of R$ 1.202.522,48 during the harvest. In the scenario where the belt filter was 12,82% above its capacity, the mud filter loss was 0,031% and the financial loss in the harvest was R$272.699,18. Finally, it was possible to conclude that the advantageous way to conduct the filtering process is with the filter below its maximum capacity. It is important to emphasize that are other evaluations that must be accomplished before suggesting an investment in the sector.
Analysis of the recovery of total reducing sugars in the filtration stage of a sugar-alcoholic plant
Keywords: Cana de açúcar; Indústria sucroalcooleira; Tratamento de caldo; Filtração; Filtro rotativo à vácuo; Filtro prensa desaguadora; Açúcares redutores totais; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA